Improving Science Teachers’ Creative Thinking Skills Using PjBL-STEAM Assisted by Canva - Widiyatmoko, Arif; Fibriana, Fidia; Aji, Septiko; Mayanti, Alfiana Nur Rosita; Darmawan, Melissa Salma; Hidayat, Luky (Universitas Negeri Semarang, 2024)
The 4Cs are the main skills emphasized to face challenges in the 21st century. One of the skills of the 4Cs is creative thinking skills. Creative thinking skills are important for students to have to solve problems with creative solutions. In addition to students, teachers as educators are also required to have these skills so that learning becomes more innovative, solution, and meaningful. The purpose of this service is to improve the creative thinking skills of science teachers in designing lessons with the PjBL-STEAM model in science learning and increase the knowledge of science teachers in utilizing Canva digital software that can be used in STEAM-based learning in science learning. The methods used in this service activity are material presentation, practice of designing posters and assembling STEAM products related to energy materials, as well as discussion and question and answer sessions. The results of the study show that PjBL-STEAM learning training assisted by Canva can improve the creative thinking skills of science teachers at Semarang City Junior High School. Participants also gave a positive response to the feasibility of the material and the presentation of the training. This means that the implementation of training to improve creative thinking skills with PjBL-STEAM, assisted by Canva Telang, was carried out very well.